Active solar dryer for biological materials - Tasić Jelena R.; Gojak Milan; Ćuprić Nenad Lj.; Božović Milan R. (FME Transactions, 2018)
This paper presents an original design and construction of a small scale, mobile, universal, ecological, chamber, active, dryer for drying medicinal and aromatic plants and non-timber forest products. The drying process uses only solar energy. The drying agent is a mixture of hot pure air and already used drying agent from the drying chamber exhaust. Pure air is heated in flat plate solar collectors and it is pulled by an electrical fan placed on the top of the drying chamber. The mobility of the collectors and dryer provides optimal utilization of sun energy throughout the day. PV modules, placed on the roof of the dryer, generate all necessary electric power for the fan, the control system and charge a set of accumulators during the day. Experimental results and kinetics of the drying process obtained by the solar dryer prototype are also given.